Aging alters DNA structure–induced genetic instability in mice - Tonia T. Li; Guliang Wang; Alexandra M. D’Amico; Laura A. Christensen; Karen M. Vasquez (Proceedings of the National Academy of Sciences, 2026)
Repetitive DNA sequences can adopt alternative (i.e., non-B) DNA structures, which represent an endogenous source of genetic instability. Z-DNA, a non-B-DNA structure, has been implicated in the development of age-related genetic disorders such as cancer and Alzheimer’s disease. Previously, we found that Z-DNA is mutagenic in mammals; however, the impact of age on Z-DNA-induced genetic instability has not yet been explored. Here, we investigated the effects of aging on Z-DNA-induced genetic instability using a transgenic mutation reporter mouse model. We found that Z-DNA was more mutagenic than control B-DNA in all tissues tested. Contrary to initial expectations, Z-DNA-induced deletions decreased with age, whereas the point mutation frequencies remained unchanged. Our results suggest that while the cleavage activities on Z-DNA were similar in both age groups, the reduction of Z-DNA-induced deletion mutants in aged mice was due to attenuated DNA end-joining efficiency, which is required for the mutagenic processing of Z-DNA, and increased apoptosis. These results provide mechanistic insight into age-associated genetic instability and the aging-cancer link.